Modulation of Apoptosis by Plant Polysaccharides for Exerting Anti-Cancer Effects: A Review - Gan, Qing-xia; Wang, Jin; Hu, Ju; Lou, Guan-hua; Xiong, Hai-jun; Peng, Cheng-yi; Huang, Qin-wan (Frontiers in Pharmacology, 2020)
Cancer has become a significant public health problem with high disease burden and mortality. At present, radiotherapy and chemotherapy are the main means of treating cancer, but they have shown serious safety problems. The severity of this problem has caused further attention and research on effective and safe cancer treatment methods. Polysaccharides are natural products with anti-cancer activity that are widely present in a lot of plants, and many studies have found that inducing apoptosis of cancer cells is one of their important mechanisms. Therefore, this article reviews the various ways in which plant polysaccharides promote apoptosis of cancer cells. The major apoptotic pathways involved include the mitochondrial pathway, the death receptor pathway, and their upstream signal transduction such as MAPK pathway, PI3K/AKT pathway and NF-κB pathway. Moreover, the paper has also been focused on the absorption and toxicity of plant polysaccharides with reference to extant literature, making the research more scientific and comprehensive. It is hoped that this review could provide some directions for the future development of plant polysaccharides as anticancer drugs in pharmacological experiments and clinical researches.